AUSTRALIAN TELECOMMUNICATIONS POLICY IN AN INTERNATIONAL CONTEXT: ISSUES FOR THE FUTURE - R.A. Joseph (Prometheus, 1996)
Australian telecommunications policy is undergoing a period of rapid change. Policy statements released to date have placed emphasis on competition and liberalisation but with a focus on the domestic situation. Australia's involvement in international telecommunications policy change has received less attention than domestic telecommunications reform issues. It is argued in this paper that the success of what Australia wants to achieve nationally through telecommunications will depend in large part on international telecommunications regulatory developments and Australia's response to them. The complexity and direction of international change in telecommunications requires a more sophisticated approach to policy development than has taken place in Australia to date. This paper sketches an outline of current trends in international telecommunications reform, Australia's response to them and identifies issues for the future. These future issues include information policy, tensions between competition policy and trade policy, industry policy, direct foreign investment, and codes of conduct for multinational companies. Some areas requiring further research are also identified.